اجتاهات معلمات رايض األطفال حنو استخدام الذكاء االصطناعي يف عمليات التدريس الفعل يف مراحل ُمان التعليم املُب ّكر مبحافظة مشال الباطنة يف سلطنة - Al Maamari, Naif Ali Amir (Penerbit Universiti Kebangsaan Malaysia, 2024)
The objective of this research is to reveal the trends of kindergarten teachers towards the use of artificial intelligence in effective teaching processes at the early levels of Education in North Al Batinah province of the Sultanate of Oman. There were 182 respondents have been selected in a simple random manner, and to achieve the research objective. The researcher used the qualitative research method and descriptive curriculum through the preparation of a questionnaire, consisting of 29 phrases, distributed in two axes: I. Kindergarten teachers' trends towards the use of artificial intelligence in teaching processes, II: Challenges facing kindergarten teachers towards the use of artificial intelligence in teaching processes, verified honesty and consistency. research findings show that the trends of kindergarten teachers towards the use of artificial intelligence in effective teaching processes at the early levels of Education in North Al Batinah governorate are highly appreciated. Besides, the degree of challenges faced by kindergarten teachers towards the use of artificial intelligence in effective teaching processes at the early levels of education in North Al Batinah governorate has been highly challenged. There are no statistically significant differences at the indicative level (α=0.05) in kindergarten teachers' trends towards the use of artificial intelligence in effective teaching processes at the early levels of Education in North Batinah, depending on research variables; (Scientific qualification, years of work experience, kindergarten course, appointment status). As the result of the research, the researcher recommended offering more courses and training workshops for kindergarten teachers on the use of artificial intelligence, including qualifying programs and plans for kindergarten teachers within the Ministry's plans, encouraging them to take advantage of electronic sites and applications of artificial intelligence. Moreover, improves the working environment, provides computers, and high-quality Internet, and benefits from leading Arab and international institutions in the field.